'If you are found taking medicine, you will be called names and considered less of a man': young men's engagement with HIV treatment and care during ulwaluko (traditional initiation and circumcision) in the Eastern Cape Province of South Africa. Issue 1 (1st January 2021) - Gittings, L.; Hodes, R.; Colvin, C.; Mbula, S.; Kom, P.
ABSTRACT: This paper explores how HIV-positive abakhwetha (young male initiates) undergoing ulwaluko (traditional Xhosa initiation and circumcision) engage with HIV-related biomedical care and treatment. Health-focused life history narratives ( n = 36), semi-structured interviews ( n = 32) and analysis of health facility files ( n = 41) with adolescent boys and young men (ages 13–24) living with HIV, and semi-structured interviews with traditional and biomedical health practitioners ( n = 14) were conducted in 2017 and 2018. This research was part of the Mzantsi Wakho study, a longitudinal, mixed methods study of adolescents living with HIV ( n = 1060). Findings demonstrate that ulwaluko rules of not engaging with biomedical care and treatment pose a challenge for initiates who are taking chronic medicine. Fears of inadvertent disclosure of their HIV-positive status collide with the pressure to successfully complete ulwaluko in order to be legitimised as men. In response to this dilemma, they engage a variety of strategies – including taking medicine in secret by hiding them, having a trusted person deliver them discretely, and stopping medicine-taking altogether. The three months following ulwaluko also pose a challenge in accessing biomedical treatment and care. In this time of high surveillance, amakrwala (new men) do not present at health facilities for fear of being thought to have had a botched circumcision or to have contravened 'manhood rules' and left ulwaluko before having healed properly. To get around this, those who continued taking medicine engaged caregiver pick-ups. Beyond suggesting that ulwaluko is a high-risk time for disengagement from biomedical treatment and care, this paper builds on a robust scholarship on the importance of locality and context in gender and health research. It documents the creativity, agency and resilience of initiates and their families as they subvert and re-signify health-related masculine norms.